Documentary description’s works at the Archivo Real y General de Navarra about the Navarra’s Conquest and Incorporation into the Crown of Castile - Segura Urra, Félix (Huarte de San Juan. Geografía e Historia, 2021)
From twenty years ago, the Archivo Real y General de Navarra is immersed in a global project, articulated through various initiatives, in order to make available to researchers the most information concerning his documentation, notably the institutional funds. At present, the study of the Conquest and Incorporation into Castile can find new ways of spreading knowledge due to the culmination of cataloging, description’s and digitization’s works of medieval documentation of Comptos, judicial documentation of the Consejo Real and Corte Mayor, and Rena’s documentation